Evaluating the Social Impact of MSME Financing and TJSL at Bank Mandiri through the Lens of Islamic Economics: Evaluasi Dampak Sosial Pembiayaan UMKM dan TJSL di Bank Mandiri Melalui Perspektif Ekonomi Islam - Felly Krisnawati; Agus Angga Rizky (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
This study examines MSME financing and social investment initiatives at Bank Mandiri through the integrated lens of inclusive and Islamic economics. Using a descriptive quantitative method and interpretive analysis, data from the 2024 Annual Report—including financial ratios and TJSL program outcomes—are analyzed. Findings show that although MSME credit volume rose nominally from IDR 114.6 trillion (2022) to IDR 135.3 trillion (2024), its share declined from 9.52% to 8.10%, indicating a portfolio shift toward corporate lending. Nonetheless, a low NPL (0.97%) and high loan loss coverage (303.85%) reveal sufficient capacity to re-expand MSME lending. TJSL programs like Rumah BUMN and Wirausaha Muda Mandiri empowered 15,000+ MSMEs, achieving high SROI (3.9–4.06) and functioning as strategic pipelines for financial inclusion. These align with Islamic values of distributive justice and ethical intermediation. A simulation estimates that restoring the MSME credit ratio to 9.0% in 2025 could increase inclusive lending by IDR 30 trillion. This study introduces a triangulated framework—financial analysis, social impact, and projections—that contributes to ethical finance literature and offers actionable insights for policy and ecosystem-based strategies